Religiosity and internal developmental assets amongst Malay adolescents in Malaysia - Yaacob, Siti Nor; Tan, Soon Aun; Abdul Rahim, Siti Marnizah; Hasbullah, Muslihah; Juhari, Rumaya; Baharudin, Rozumah (Canadian Center of Science and Education, 2015)
This study aimed to examine the relationship between religiosity and internal developmental assets amongst Malay adolescents in Malaysia. A total of 737 school-going Malay adolescents were recruited by using multistage cluster sampling method from four states (Selangor, Kedah, Kelantan and Johor) of Peninsular Malaysia. The results of the study indicated that Malay adolescents have good Islamic knowledge and practices, and in general they have good internal developmental assets. Both Islamic worldview (knowledge) and personality (practices) were found to have positive significant relationships with overall internal develop mental assets and its specific domains. Precisely, Islamic personality denoted to be the strongest predictor in determining Malay adolescents’ internal developmental assets. Religious-based intervention should be emphasized to enhance adolescents’ internal developmental assets.